Analysis of Financial Management with a Reference of Municipal Corporations: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The phenomenon of urbanization is neither new nor surprising. During the ages people have tended to cluster together for their living and in due course of time areas in habited by human beings for purposes other than agriculture got designated as urban. Of course, invariably there are other attributes too but these are in the nature of afterthoughts and refinements, and mainly to distinguish the viable units from the non-viable ones and do not deserve to be considered as characteristic of the scene. One may, indeed, be tempted to make a broad generalization to help identification clusters where human beings are found together basically and initially for purely social reasons maybe termed as non-urban areas where economic necessity brings them together are generally urban. That is so far as sociological factors go too. Naturally, with the evolution of human society and complexities added to human activity, even the rural areas have gradually begun to get transformed into economic entities. Agriculture has already become an industry in many countries and is well on its way to show these characteristics in India as well. A way of life is getting changed to a way of living. Consequent changes in social habits, family and institutional relationships and the predominance of economic attitudes and pressures are already abundantly visible. All this is profoundly disturbing to the romantic view of human society, but is undoubtedly a blessing in the present stage of human evolution. Thanks to the unabashed maintained of double standards, the human element in the rural areas was relegated into the background and treated with apathy, if not contempt undeserving in the eyes of the urban dweller of the good things of life. The producer of milk and food and vegetables had become a second class citizen, whereas the manufacturer of pins and needles in the miserable slums of an urban area was the better citizen Naturally, such a state of affairs could not last indefinitely and the exodus to towns from the rural areas began many decades ago. In some countries, the saturation-point has been reached already. In India the process continues unabated though the magnitude of the problem is not fully realized everywhere for various reasons.